PLD13 A Questionnaire to Measure Parents' Experiences and Satisfaction with Care During Very Preterm Birth: A Validation Study. (9th June 2014) - Sawyer, A; Rabe, H; Abbott, J; Gyte, G; Duley, L; Ayers, S
Abstract : Background: Preterm birth is a major challenge in perinatal healthcare. However, there is little research into parents' satisfaction with care during very preterm birth. Therefore the aim of the current study was to develop and evaluate a questionnaire to measure parents' experiences and satisfaction with care during very preterm birth. Methods: A 30-item questionnaire (The Preterm Birth Experience and Satisfaction Scale; P-BESS) was developed on the basis of interviews with 39 parents of very preterm babies, a literature review, and discussion with relevant experts. The questionnaire was posted to parents at five tertiary neonatal units and its reliability and validity explored. Results: 458 parents were invited to take part and 147 (32%) responded. Psychometric analyses suggested a 17-item questionnaire with three subscales: (1) Staff professionalism and empathy, (2) Information and explanations, and (3) Confidence in staff. The total scale and subscales showed high reliability and there was evidence of convergent validity. For women whose partners were present at the birth, a fourth factor can be added on "Partner Involvement". Conclusions: The P-BESS is the first questionnaire developed specifically to measure experiences and satisfaction for preterm birth. Findings suggest that it is a reliable and valid measure. The total score may be useful to compare across hospitals and differing practices, whereas individual aspects of the care environment can be evaluated using the subscales. Caution should be taken when administering to fathers as the same factor structure was not identified in fathers as mothers.